Harbingers of dissolution? Grain prices, borders and nationalism in the Habsburg economy before the First World War - Nikolaus Wolf; Max-Stephan Schulze (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
This paper explores the pre-First World War Austro-Hungarian economy as a prominent case where growing conflict between various ethnic and national groups within an empire might have contributed to the emergence of internal borders and even its eventual dissolution. To this end we adopt an Engel-and-Rogers-type approach to examine on an annual basis the extent of co-movements in grain prices across a sample of ten regional capital cities in the empire and over the period 1877-1910. There are two key findings. First, the political borders that emerged from 1918 onwards became visible in the price dynamics of grain markets already 20 years before the Great War. Second, this effect of a 'border before a border' can be explained by the extent of language heterogeneity across the various parts of the Habsburg Empire. These results raise several important questions about both the forces that shaped pre-war market integration as well as the economic costs of breaking up the Habsburg customs union after 1918.
Keywords: N13; F15; Z13; 330; Border Effects; Grain Prices; Habsburg Empire; Market Integration; Nationalism; Pre-1914 Europe; Getreidepreis; Staatsgebiet; Nationalismus; Mathematische Ökonomie; Wirtschaftsgeschichte; Österreich-Ungarn